Is Nighttime Really Not the Right Time for a Laparoscopic Cholecystectomy? - Anna C. M. Geraedts; Meindert N. Sosef; Jan Willem M. Greve; Mechteld C. de Jong (Canadian Journal of Gastroenterology and Hepatology)
Purpose. The impact of an out-of-hours laparoscopic cholecystectomy on outcome is controversial. We sought to determine the association between an out-of-hours procedure and postoperative complications within 90 days. Methods. Between 2014 and 2016, 1553 laparoscopic cholecystectomies were performed. Therapeutic, operative, and outcome data were prospectively collected and analyzed. We defined out of hours as during weekends, national holidays, and daily between 5PM and 8AM. Results. Most patients operated on were female (n=988; 63.6%) and the majority of procedures were electives (n=1341; 86.3%). Although all procedures were performed with a laparoscopic intent, 42 (2.7%) were converted to open procedure. In total, 145 (9.3%) procedures were out of hours, all nonelective, and in most cases for acute cholecystitis (n=111; 7.1%). Overall, there were 212 complications in 191 patients (12.3%), most (n=153; 9.9%) classified as minor. The conversion rate in the out-of-hours group was significantly higher (9.7% vs 2.0%; p<0.001). While univariate analyses revealed out-of-hours procedure (OR=1.83; p=0.008) to be associated with an increased risk of complications, when controlling for confounding factors by multivariate analysis, this association was not found. However, operation by surgical staff (OR=1.71) and conversion to laparotomy (OR=3.74) were found to be independently associated with an increased risk of complications (both p<0.05), while an emergency procedure tended to be associated with postoperative morbidity (OR=1.82; p=0.069). Conclusion. An out-of-hours laparoscopic cholecystectomy was not found to be an independent risk factor for developing postoperative morbidity and time of day should therefore only be a relative contraindication.